ANALISIS PENGARUH FAKTOR BUDAYA DAN SOSIAL TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK SAMSUNG - Muhammad Nur Aminudin; Muhammad Anang Firdaus; Ira Eka Pratiwi (OIKONOMIKA: Jurnal Kajian Ekonomi dan Keuangan Syariah, 2020)
This study aims to analyze the influence of cultural and social factors on the purchasing decision of Samsung brand smartphones on IAIN Fattahul Muluk Papua Students. This type of research uses quantitative research. The population in this study were students of IAIN Fattahul Muluk Papua. The number of samples obtained was 280 students, consisting of 68 students of the Faculty of Islamic Economics and Business, 64 students of the Faculty of Syariah, and 148 students of the Faculty of Tarbiyah. Data were collected using a questionnaire, while data analysis techniques used is Multiple Linear Regression. This research shows that cultural factors have a positive and significant influence on the purchasing decisions of Samsung brand smartphones, while social factors have a positive but insignificant effect on the purchasing decisions of Samsung brand smartphones. Furthermore, the influence of cultural factors and social factors simultaneously have a positive and significant effect on purchasing decisions Samsung smartphone brand.